NIPAH VIRUS INFECTION: A GROWING DEADLY PARAMYXOVIRUS AND THE RECENT STATUS OF POTENTIAL THERAPEUTICS IN INDIA - Singh, Asheesh; Singh, Parul (Journal of Drug Delivery and Therapeutics, 2018)
Nipah virus is an RNA virus that is part of the Paramyxovidae family that was first identified as a zoonotic pathogen after an outbreak involving severe respiratory illness in pigs and encephalitic disease in humans in Malaysia and Singapore in 1998 and 1999. Nipah virus can cause a range of mild to severe disease in domestic animals such as pigs. Nipah virus infection in humans causes a range of clinical presentations, from asymptomatic infection (subclinical) to acute respiratory infection and fatal encephalitis. Nipah virus can be transmitted to humans from animals (bats, pigs), and can also be transmitted directly from human-to-human. Fruit bats of the Pteropodidae family are the natural host of Nipah virus. There is no treatment or vaccine available for either people or animals. A recombinant measles virus (rMV) vaccine expressing NiV envelope glycoproteins is proposed but is still under trial. The primary treatment for humans is supportive care. Nipah virus is an emerging threat to the human life with history of outbreaks chiefly in Bangladesh, India & Malaysia. Categorized as zoonotic biosafety level 4 (BSL4) agent depending upon the geographic locations of outbreaks, it is responsible of case mortality between 40% to 100% in both humans and animals thus one of the most deadly virus known to infect humans. The present review article cover current potential therapeutics in India against nipah virus infection. Keywords: Nipah, Virus, Infection, Hendra virus, paramyxoviruses, Human being